Tele-education in emergency care. Issue 11 (22nd October 2007) - Binks, S; Benger, J
Abstract : The use of telemedicine is becoming routine and accepted in certain limited areas such as electrocardiogram and radiograph/computed tomographic scan telemetry. Tele-education has thus far had limited applications although in emergency medicine it has been shown to be an effective medium for the education of senior house officers and emergency nurse practitioners in remote or peripheral units. Despite apparent clinical and cost benefits and government support, the full potential of two way video conferencing and tele-presence has yet to be realised by the clinician, educator and manager.